Proteolytic activation of c-MYC facilitated by DOT1L - Gian P. Sepulveda; Karol Nawalaniec; Iana Nikorich; Ekaterina S. Guschanskaia; Alexandra Mora-Martin; Ruben Esse; Ainhoa Ceballos; Chaoshuang Xia; Julian Kwan; Benjamin C. Blum; Andrew Emili; Maria D. Cardamone; et al. (Proceedings of the National Academy of Sciences, 2026)
c-MYC is a key regulator of growth and metabolism. Functional and molecular cooperation between the H3K79 methyltransferase DOT1L and c-MYC has been reported in several human cancer types, but the nature of their interaction remains undefined. We demonstrate that DOT1L and MYC [Myc and Mondo-like (MML-1) in Caenorhabditis elegans ] coregulate genes in the nematode model and mammalian cancer cells. Moreover, both c-MYC and MML-1 exhibit cleavage products facilitated by DOT1L function. Surprisingly, we found a similarity between a conserved sequence in DOT1 proteins and the DDI-family protease catalytic motif. We characterize a c-MYC sequence preceding the DNA-binding domain as a site of nuclear proteolytic cleavage, demonstrate its importance for transcription activation by c-MYC, and propose that c-MYC is activated by a protease, as previously reported for Nuclear factor erythroid 2-related factor (NRF) and SREBP transcription factors. Our results suggest that DOT1L may activate c-MYC and other transcription factors in the nucleus by acting as a protease.